Two-Weight Criteria for the Multidimensional Hardy-Type Operator in p-Convex Banach Function Spaces and Some Applications - Bandaliyev, R. A. (Ukrains’kyi Matematychnyi Zhurnal, 2015)
The main aim of the paper is to prove a two-weight criterion for the multidimensional Hardy-type operator from weighted Lebesgue spaces into p-convex weighted Banach function spaces. The problem for the dual operator is also considered. As an application, we prove a two-weight criterion of boundedness of the multidimensional geometric mean operator from weighted Lebesgue spaces into weighted Musielak–Orlicz spaces.